2007
DOI: 10.1007/s10509-007-9549-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetic fields on the formation of circumstellar discs around young stars

Abstract: We present first results of our simulations of magnetic fields in the formation of single and binary stars using a recently developed method for incorporating Magnetohydrodynamics (MHD) into the Smoothed Particle Hydrodynamics (SPH) method. An overview of the method is presented before discussing the effect of magnetic fields on the formation of circumstellar discs around young stars. We find that the presence of magnetic fields during the disc formation process can lead to significantly smaller and less massi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…They found that the formation of a RSD is suppressed as long as λ is of order 5 or less. However, the λ = 5 case in Price & Bate's (2007) SPMHD simulations appears to have formed a small disk (judging from the column density distribution). It is unclear whether the disk is rotationally supported or not, since the disk rotation rate was not given in the paper.…”
Section: Magnetic Braking Catastrophe In Ideal Mhd Limitmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that the formation of a RSD is suppressed as long as λ is of order 5 or less. However, the λ = 5 case in Price & Bate's (2007) SPMHD simulations appears to have formed a small disk (judging from the column density distribution). It is unclear whether the disk is rotationally supported or not, since the disk rotation rate was not given in the paper.…”
Section: Magnetic Braking Catastrophe In Ideal Mhd Limitmentioning
confidence: 98%
“…Misalignment between the magnetic field and rotation axis as a way to form large RSDs has been explored extensively by Hennebelle and collaborators (Hennebelle & Ciardi 2009;Ciardi & Hennebelle 2010;Joos et al 2012; see also Machida et al 2006;Bate 2007, andKeiser 2013). The misalignment is expected if the angular momenta of dense cores are generated through turbulent motions (e.g., Burkert & Bodenheimer 2000;Seifried et al 2012b;Myers et al 2013;Joos et al 2013).…”
Section: Magnetic Field-rotation Misalignmentmentioning
confidence: 99%
“…Recent numerical simulations have shown that even a weak magnetic field can have noticeable dynamical effects. It can alter how cores fragment (Price & Bate, 2007bHennebelle & Fromang, 2008;Hennebelle & Teyssier, 2008;Peters et al, 2011), change the coupling between stellar feedback processes and their parent clouds (Nakamura & Li, 2007;Krumholz et al, 2007b), influence the properties of protostellar disks due to magnetic braking (Price & Bate, 2007a;Mellon & Li, 2009;Hennebelle & Ciardi, 2009;Seifried et al, , 2012aSeifried et al, ,b, 2013, or slow down the overall evolution (Heitsch et al, 2001a).…”
Section: Magnetic Field Structurementioning
confidence: 99%
“…The simplified framework of the ideal magnetohydrodynamics (MHD) used in the first studies led to the disappearance of the large Keplerian disks that are easily formed in hydrodynamical simulations as a result of the very effective magnetic braking created by a strong pile-up of magnetic flux towards the centre of the collapsing system (Galli et al 2006;Allen et al 2003, Price & Bate 2007Hennebelle & Teyssier 2008;Matsumoto & Tomisaka 2004;Hennebelle & Fromang 2008;Commerçon et al 2010). In these simulations, disks were found to form only for unrealistically weak magnetic field intensities (corresponding to a mass-to-flux ratio more than 10 times the critical value derived by Mouschovias & Spitzer 1976).…”
Section: Introductionmentioning
confidence: 99%